Effects of alcohol enrichment on thermochemical fuel reforming (TFR): Insights from chemical kinetics. (1st January 2021) - Zhu, Lei; Li, Ang; Zhang, Zhenyingnan; Li, Bolun; Ma, Chao; Cheng, Xiaogang; Zou, Xinyao; He, Zhuoyao; Lu, Xingcai; Huang, Zhen
Abstract: Thermochemical fuel reforming (TFR) is an innovative strategy in spark-ignition natural gas (NG) engines. According to this strategy, methane can be reformed into hydrogen and carbon monoxide with alcohol enrichment. In this study, effects of five kinds of alcohols on TFR were investigated. Differences of alcohols were classified into three parameters: OH/C ratio, hydroxyl numbers and isomerism, which were investigated in the laminar flow reactor platform. Experimental results demonstrated that methanol was regarded as the best enrichment fuel. Kinetic analysis indicated that alcoholic structure was strongly associated with concentrations of crucial radicals such as H, OH and HO2, which contributed to methane oxidation. Therefore, normal alkyl alcohols with less OH/C ratio and more hydroxyl numbers exhibited greater reactivity, which helped to the formation of CO and H2 . Furthermore, this kinetic model was employed in engine simulations, and methanol has been proved to be a promising fuel for TFR engines. Highlights: Molecular structures of alcohols have significant influence on TFR performance. Kinetic studies revealed the oxidation pathways of CH4 with alcohol enrichment. Larger amount of H2 and CO would be formed with methanol enrichment.